Keyless bike starter / Muhammad Najib Mohd Zailani ... [et al.] - Mohd Zailani, Muhammad Najib; Mohd Sharil, Basyir; Wan Saiful, Syed Abdul Rahman; Kahardy, Syafiq; A Nor Azmi, Muhammad Amirul Safiq; Thominathan, Santhanamery (2020)
Motorcycles are considered as one of the most popular mode of transportation in Malaysia. It is used by people of all ages and gender. However, there are some common problems faced by majority of the motorcyclist when using key based system. One of the problems faced is misplacing the keys or loss of the keys. Besides, the kick starter that exist in current motorcycles is not convenient to certain users particularly women and elderly people where it needs a high energy to start the motorcycles. In order to solve the problem a new product called Keyless Bike Starter (KBS) is designed and developed using the Internet of Things (IoT) and Radio Frequency Identification (RFID) technology. The KBS will replace the old method of starting the motorcycles with RFID scanner and smartphone. These technologies can help to overcome the above mention problems whereby the motorcycles will automatically start when the registered access card is being scanned through the scanner. The motorcycles can also be started by using an application on user smartphones whereby the button on the application need to be triggered to start up the motorcycle. Without the registered access card and the correct smartphone, the motorcycles cannot be started.